Systematic investigation of phthalocyanines, naphthalocyanines, and their aza-analogues. Effect of the isosteric aza-replacement in the core1. Issue 29 (7th August 2015) - Novakova, Veronika; Reimerova, Petra; Svec, Jan; Suchan, Daniel; Miletin, Miroslav; Rhoda, Hannah M.; Nemykin, Victor N.; Zimcik, Petr
<x xml:space="preserve">Abstract</x> A series of zinc complexes of phthalocyanines, naphthalocyanines and their aza-analogs was studied and compared using UV-vis and MCD spectra, molecular calculations, and photophysical and electrochemical measurements.